School Readiness in Implementing Kurikulum Merdeka: A Case Study in SMAN 15 Bandar Lampung - Fitriyani; Yanuar Dwi Prastyo (Nusantara Journal of Multidisciplinary Science, 2024)
The research investigates the readiness of SMAN 15 Bandar Lampung in implementing the "Kurikulum Merdeka," with a particular focus on the "Projek Penguatan Profil Pelajar Pancasila" (P5). The study identifies key challenges faced by schools in adopting this new curriculum, including resource availability, teacher preparedness, and administrative support. Through a combination of observation and interviews, the researcher explores the school’s strategies and the effectiveness of their implementation. Findings highlight significant efforts by the leadership and staff, yet reveal gaps in infrastructure, financial resources, and teacher training. The study concludes that while SMAN 15 Bandar Lampung has made commendable progress, further investment in resources and comprehensive capacity-building programs is needed to ensure the successful adoption of the Kurikulum Merdeka. This research provides insights into the potential barriers and recommendations for schools across Indonesia.